2023
DOI: 10.3390/agronomy13061529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Long-Term Straw Return and Nitrogen Fertilization on Wheat Productivity and Soil Properties in the Wheat-Maize-Soybean Rotation System in the Pannonian Plain

Abstract: The study, conducted to evaluate the effects of long-term straw management combined with the application of increasing nitrogen rates on the yield of twenty winter wheat varieties, as well as on soil properties, was carried out in a long-term field trial established in 1971. The trial was monitored for twenty growing seasons under rainfed conditions in a typical chernozem zone of the southern part of the Pannonian Plain. The cropping system was a winter wheat-maize-soybean rotation. The ten SN-treatments (comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
4
11
0
Order By: Relevance
“…The significant effect of co-application of straw returning and chemical fertilization on the crop yields in the study site was in agreement with several recent studies [ 4 , 54 , 55 ]. Shan et al [ 54 ] suggested that higher crop yields in the straw amended soils primarily attributes to the long-term significant inputs of C and nutrients by straw [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…The significant effect of co-application of straw returning and chemical fertilization on the crop yields in the study site was in agreement with several recent studies [ 4 , 54 , 55 ]. Shan et al [ 54 ] suggested that higher crop yields in the straw amended soils primarily attributes to the long-term significant inputs of C and nutrients by straw [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, the determination of the optimal duration always needs to consider the local environment. Many studies have waged an exploration based on their local environment [25,38,39]. Under long-term straw return, Goran et al and Wang et al discovered the content of TN significantly increased [14,25], which was similar to our outcome.…”
Section: Straw Durationsupporting
confidence: 87%
“…Many studies have waged an exploration based on their local environment [25,38,39]. Under long-term straw return, Goran et al and Wang et al discovered the content of TN significantly increased [14,25], which was similar to our outcome. One study suggested that long-term straw returning over 20 years could considerably increase SOC content by two or three times compared with short-term straw returning [52].…”
Section: Straw Durationsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, it was determined in previous studies that incorporating straw mulching with these tillage practices had multiple benefits. It improved soil quality and nutrients while also significantly reducing surface runoff volume [10][11][12]. This effect was particularly noticeable when tillage practices were combined with straw mulching, resulting in decreased outflow concentrations and reduced volumes of large-size colloids in surface and subsurface runoff.…”
Section: Introductionmentioning
confidence: 99%